A REVIEW OF INTER CELL INTERFERENCE MANAGEMENT IN REGULAR AND IRREGULAR GEOMETRY CELLULAR NETWORKS (Jurnal Teknologi (Sciences & Engineering), 2021)
This paper reviews the inter-cell interference (ICI) mitigation approaches in the OFDMA based multicellular networks with more emphasis on the frequency reused based ICI coordination schemes in the downlink systems. The geometry of the network severely affects the Signal to Interference and Noise Ratio (SINR); therefore, the wireless cellular systems are strongly dependent on the spatial BSs configuration and topology of a network. ICI mitigation techniques for both regular and irregular geometry networks are analyzed and a qualitative comparison along with the future research directions are presented.